MODEL STRUKTURAL DESAIN PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA INDUSTRI ENERGI - Sari Sakarina; Ade sima pertiwi; Djatmiko Noviantoro (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the effect of job design and work environment on employee performance, with job satisfaction as a mediating variable in the energy industry. The research employs a quantitative approach with an explanatory research design and a cross-sectional method. The study population consists of 200 permanent employees, with a sample of 134 respondents determined using the Slovin formula and stratified random sampling technique. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) through SmartPLS 4. The results indicate that job design and work environment have a positive and significant effect on job satisfaction and employee performance. Job satisfaction is proven to have a significant effect on employee performance and partially mediates the relationship between job design and work environment on employee performance. The R² value shows that the model has strong predictive power. These findings strengthen the integration of the Job Characteristics Model and Environmental Psychology Theory within the context of the Indonesian energy industry.